2010
DOI: 10.1021/la102806v
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Layer-by-Layer Assembly of Graphene Multilayer Films for Enzyme-Based Glucose and Maltose Biosensing

Abstract: We have developed an unconventional method for the layer-by-layer (LbL) assembly of graphene multilayer films. Unconventional LbL assembly was achieved by the following two-step process. Graphene sheets were modified by pyrene-grafted poly(acrylic acid) (PAA) in aqueous solution, and then the modified graphene sheets were used for layer-by-layer alternating deposition with poly(ethyleneimine) (PEI). The graphene-multilayer-film-modified electrode shows enhanced electron transfer for the redox reactions of Fe(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(94 citation statements)
references
References 63 publications
0
90
2
1
Order By: Relevance
“…This enables the controlled release of the biocide and, therefore, provides a safe environmental loading of the biocide together with specific targeting. A similar technology of nano-containers loaded with active compounds is already used in drug delivery [13], medical sensory applications [14], and for protection against corrosion [15]. Similarly, the technology of nano-containers for antifouling purposes has been explored in order to assess antifouling applications.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the controlled release of the biocide and, therefore, provides a safe environmental loading of the biocide together with specific targeting. A similar technology of nano-containers loaded with active compounds is already used in drug delivery [13], medical sensory applications [14], and for protection against corrosion [15]. Similarly, the technology of nano-containers for antifouling purposes has been explored in order to assess antifouling applications.…”
Section: Introductionmentioning
confidence: 99%
“…78 L-b-L assembly approach is a firmly established technique where electrostatic interaction enables the alternating assembly of positively and negatively charged GO sheets thereby providing high degree of control over the thickness of films. [79][80][81] However, LB technique is the most promising alternating method to assemble amphiphilic molecules at the air-water interface as it enables precise control over the monolayer thickness and gap between them, providing homogeneous deposition of the monolayer over large areas and could be useful to make hybrid films with varying layer composition. [82][83][84][85][86] Furthermore, lithography and various printing strategies have also been used for patterning graphene that have been acquired from the CVD method for sensing application.…”
Section: Synthesis and Assembly Approaches Toward Biosensing Platformmentioning
confidence: 99%
“…The hybrid biosensors showed the fast response time of ∼3 s, the sensitivity of 3.8 µA mM −1 cm −2 , the limit of detection of 170 µM, and the linear detection range of 2-20 mM for the flow-injection amperometric detection of glucose. Zeng et al demonstrated an unconventional method for the LbL assembly of graphene multilayer films using PAAc and poly(ethyleneimine) [109]. They demonstrated this concept by combining the graphene multilayer with a bienzyme system of GOx and glucoamylase for the fabrication of a maltose amperometric biosensor for glucose and maltose.…”
Section: Enzymatic Biosensorsmentioning
confidence: 99%